2015
DOI: 10.1038/srep14774
|View full text |Cite
|
Sign up to set email alerts
|

Identification of H2S3 and H2S produced by 3-mercaptopyruvate sulfurtransferase in the brain

Abstract: Hydrogen polysulfides (H2Sn) have a higher number of sulfane sulfur atoms than hydrogen sulfide (H2S), which has various physiological roles. We recently found H2Sn in the brain. H2Sn induced some responses previously attributed to H2S but with much greater potency than H2S. However, the number of sulfur atoms in H2Sn and its producing enzyme were unknown. Here, we detected H2S3 and H2S, which were produced from 3-mercaptopyruvate (3 MP) by 3-mercaptopyruvate sulfurtransferase (3MST), in the brain. High perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
204
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(224 citation statements)
references
References 40 publications
10
204
0
1
Order By: Relevance
“…Actual reports of cellular RSS concentrations are rare, but preliminary studies provide concentrations that equal or exceed ROS (18,27). This is further supported by our calculations, above, of sulfur and oxygen turnover.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Actual reports of cellular RSS concentrations are rare, but preliminary studies provide concentrations that equal or exceed ROS (18,27). This is further supported by our calculations, above, of sulfur and oxygen turnover.…”
Section: Discussionsupporting
confidence: 79%
“…Persulfides and polysulfides can also be produced by two-electron oxidation of organic sulfur (cysteine) and transferred to a protein thiol (e.g., 3-mercaptopyruvate sulfur transferase, 3MST), forming 3MST persulfide (3MST-S-S). The hydrogen persulfide, H 2 S 3 , has recently been shown to be formed from 3MST persulfide in neuronal cells, and it may exist in micromolar concentrations (27). H 2 S can also reduce a disulfide bond (RSSR= ϩ H2S ¡ RSSH ϩ R'S).…”
Section: Discussionmentioning
confidence: 99%
“…Others and we have also reported that H 2 S can be mobilized from biochemical reservoirs such as acid labile sulfur (iron sulfur clusters), and sulfane sulfur (e.g. thiosulfide, protein per/polysulfide) [23], [36], [37]. Moreover, increasing evidence suggests that sulfane sulfur serves as an active form of H 2 S that is highly potent and may be responsible for some of H 2 S biological effects [18], [29].…”
Section: Introductionmentioning
confidence: 65%
“…Sulfide and polysulfide were detected with colorimetric assays (12). Thiosulfate and sulfite were detected after monobromobimane (mBBr) derivatization by using high-pressure liquid chromatography (HPLC) (12,47). Polysulfide was produced by mixing 13 mg of sulfur power and 70 mg of sodium sulfide in 5 ml of anoxic distilled water under argon gas, as previous described (12).…”
Section: Methodsmentioning
confidence: 99%